Development prospects of keratoplasty in Moscow - E. M. Kildyushov; A. V. Zolotorevsky; O. A. Doronina; A. A. Agafonova (Oftalʹmologiâ, 2014)
A retrospective analysis of the statistical data for the years 2010‑2012 on mortality and the donor selection of the Bureau of Forensic Pathology of Moscow, Department of Forensic Pathology of Pirogov N. I. Russian National Research Medical University and ILab Eye Bank in order to determine the possible number of keratoplastic surgeries. The results of statistical data analysis testify to the fact that the number of available donor material is not sufficient to meet the needs for keratoplastic material and it is necessary to create eye banks, which would have provided this need. It is necessary to create eye banks, that possess a clear logistics chain of intake donor tissue, preliminary assessment of the donor tissue, laboratory diagnostics of the donor’s blood and delivery of tissue to the Bank. Theeye bank should not only produce preserved material for keratoplasty, but also carry out full morpho-functional assessment of material and its subsequent delivery to consumers in health facilities.